The Influence of Work-Life Balance and Non-Physical Work Environment on Employee Performance Through Job Satisfaction: at Bank UMKM East Java Regional Office of Madura - Alham, Arfi Abdillah; Swasti, Ika Korika; fauzi, akhmad (Management Science Research Journal, 2025)
This study aims to analyze the effect of work-life balance and non-physical work environment on employee performance, with job satisfaction as an intervening variable, at the East Java Regional Office of Madura for UMKM Bank. The population in this study consists of 100 employees working in the Credit Division, General & HR Division, and Customer Service Division from the Bangkalan, Sampang, Pamekasan, and Sumenep branch offices. The sample was selected using the census method, where the entire population is used as respondents. Data was collected and analyzed using SmartPLS software. The results show that: (1) Work-life balance contributes to improving employee performance by providing clarity in tasks and responsibilities that align with competencies, (2) The non-physical work environment also contributes to improving employee performance by motivating employees to demonstrate their best potential, (3) Work-life balance has a positive impact on employee performance through increased job satisfaction, as employees feel more satisfied with well-structured work, (4) The nonphysical work environment contributes to performance improvement through job satisfaction due to objective leadership policies in providing assessments.